Urban sprawl and microclimate in the Ga East municipality of Ghana - Kwasi Frimpong; Darko Eugene Atiemo; E.J. Van Etten (Heliyon, 2022)
Climatic elements such as temperature and rainfall provide great and unquantifiable benefits to human health. However, rapid urban sprawl has the tendency to undermine these health consequences. The relationship between urban sprawl and microclimate in the Ga East Municipality has been assessed to present the extent of sprawl that inhibit temperature and rainfall in recent times. Methodologically, satellite imagery and meteorological data (minimum and maximum temperature and rainfall) from 1990 to 2020 were used. The results indicate that rapid urban sprawl in recent times has significantly undermined the local climate through land use and land cover changes. There was strong statistical relationships between temperature and built-up areas (p < 0.05), grass/shrub cover (p < 0.04) and all vegetation cover (p < 0.03). There was also strong statistical relationship between rainfall and built-up areas (p < 0.03), grass/shrub cover (p < 0.04) and all vegetation (p < 0.02). Thus, expansion in built up areas and reduced grass/shrub cover led to increases in temperature, rainfall and surface water run off while reduction in all vegetation led to increase in both temperature and rainfall. These changes in climate brought about by urban sprawl will affect crop production, increase cataclysmic floods as well as growth of some harmful insects. There is the need for the amalgamation of urban growth and climate change into spatial planning through an all-embracing approach.